2001
DOI: 10.1021/jp011326c
|View full text |Cite
|
Sign up to set email alerts
|

Disilane Internal Rotation

Abstract: Energetics of hindered rotation in disilane are analyzed and compared to ethane. In disilane weakened (rotationally governed) hyperconjugative interactions, paramount in controlling the ethane barrier, leave the nonrotational part of the torsional coordinate as the primary contribution to disilane barrier energetics. In this regard, the 0.012 Å Si-Si bond lengthening that accompanies rotation is found to account for most of the 1.0 kcal/mol barrier. Although both the Si-Si bond expansion in disilane and the 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
26
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
(66 reference statements)
5
26
0
1
Order By: Relevance
“…Our results agree favorably with similar methods reported in the accurate work by Cho et al [6]. From the optimized geometries we conclude that the magnitude of the rotational energy red-shift is 0.043 eV (1.0 kcal/mol), which is comparable to the experimental result of 1.26 kcal/mol [15] and to the theoretical calculations of Pophristic et al [5] and of Cho et al [6]. This energy corresponds to a temperature of around 500 K, which is much higher than the typical experimental temperatures (as in CVD [16]), and implies that at low temperatures a mixture of both conformations will be found.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Our results agree favorably with similar methods reported in the accurate work by Cho et al [6]. From the optimized geometries we conclude that the magnitude of the rotational energy red-shift is 0.043 eV (1.0 kcal/mol), which is comparable to the experimental result of 1.26 kcal/mol [15] and to the theoretical calculations of Pophristic et al [5] and of Cho et al [6]. This energy corresponds to a temperature of around 500 K, which is much higher than the typical experimental temperatures (as in CVD [16]), and implies that at low temperatures a mixture of both conformations will be found.…”
supporting
confidence: 92%
“…For the staggered conformation the vibrational frequencies agree successfully with experimental values [15] and the results computed by Cho et al [6]. The major difference is noticed for the A 1g rotation symmetry, whose blue-shift is an indication 392 108.3 108.5 [5], 108.08 [6] that the molecule in the eclipsed conformation requires more oscillation energy. Instead, for the Si-Si stretching mode we obtain a frequency red-shift of only 10-20 cm À1 relative to the staggered conformation, indicating an increase of Si-Si bond length (less rigid bond).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…The morphological parameters of the eclipsed and staggered silane conformations were recently calculated by Pophristic and co-workers (1). They concluded that the origin of the eclipsed to staggered relaxation is related to the preferential hyperconjugative stabilization (meaning energy stabilization through electron excitation to a delocalized state).…”
Section: Introductionmentioning
confidence: 98%